Is House Dust Mite Specific Sublingual_x000D_ Immunotherapy Successful in Termination of Inhaled_x000D_ Corticosteroid Treatment in Children with Asthma - (:unkn) unknown (My University, 2018)
Objective: House dust mite (HDM)- specific sublingual immunotherapy (SLIT) has long-term effects contrary to pharmacotherapyin children with asthma. We aimed to study the long-term effects ofSLIT on inhaled corticosteroid usage.Material and Method: Fifty-four asthmatic children who receivedHDM -specific SLIT for at least 3 years and were followed up fora minimum 5 years after cessation of SLIT in addition to pharmacotherapy and 23 patients who received only pharmacotherapyduring the same time period were admitted in the study. SLIT andpharmacotherapy groups were evaluated retrospectively by scanning their medical records in regard to their inhaled corticosteroid(ICS) dose (μg/day), duration (month(s)/year) of ICS, and pulmonary function test (PFT) parameters. Visual analogue scores andsymptom scores recorded for 6 months in their daily record cardsgiven to them were evaluated, and dose (μg/day), and duration ofICS therapy (month(s)/year) were calculated PFTs were performedfor each patient. Based on the diary card records regardingsymptoms, the need for ICS and FEV1%, the patients were grouped as 37 SLIT-responders, 17 SLIT-nonresponders, 15PT-responders, and 8 PT-nonresponders.Results: Reduction in ICS dose was significantly higher for SLIT(407±252 μg)n group in comparison to pharmacotherapy group(224±174 μg) (p=0.009). Duration of ICS usage reduced by 63%(p=0,001) in SLIT-nonresponder group, but in pharmacotherapynonresponder group it decreased by only 11% (p=0,108).Conclusion: SLIT was effective in reducing ICS dose. Duration of ICStreatment did not decrease in the course of time in PT-nonrespondergroup while decreased in SLIT-nonresponder group.

Amaç: Ev tozu akarı (HDM) spesifik sublingual immünoterapinin_x000D_ (SLIT) astımlı çocuklarda farmakoterapinin (PT) aksine uzun_x000D_ süreli etkileri vardır. SLIT’in inhale kortikosteroid kullanımı üzerine uzun süreli etkilerini incelemeyi amaçladık._x000D_ Gereç ve Yöntem: En az 3 yıl boyunca HDM’ye spesifik SLİT_x000D_ almış ve SLIT tedavisinden sonra en az 5 yıl takip edilmiş 54_x000D_ astımlı çocuk ve aynı dönemde yalnızca farmakoterapi almış 23_x000D_ çocuk çalışmaya alındı. SLIT ve farmakoterapi grupları, ICS’nin_x000D_ inhale kortikosteroid (ICS) dozu (μg/gün) ve süresi (ay/yıl)/yıl,_x000D_ solunum fonksiyon testi (PFT) parametreleri açısından tıbbi_x000D_ kayıtlardan retrospektif olarak değerlendirildi. Tüm hastaların, 6_x000D_ ay boyunca kendilerine verilen günlük kartlardaki görsel analog_x000D_ skor ve semptom skorları değerlendirildi ve kullanılan ICS dozu_x000D_ (μg/gün) ve süresi (ay/yıl) hesaplandı, PFT testi yapıldı. Günlük_x000D_ kart kayıtlarındaki semptom, ICS ihtiyacı ve %FEV1’e göre,_x000D_ hastalar 37 SLIT-yanıtlı, 17 SLIT-yanıtsız, 15 PT-yanıtlı, 8_x000D_ PT-yanıtsız olarak gruplandırıldı._x000D_ Bulgular: ICS dozunda azalma, SLIT (407±252 μg) için farmakoterapi grubuna (224±174 μg) kıyasla anlamlı olarak daha yüksekti (p=0,009). SLIT-yanıtsız grupta ICS kullanım süresi % 63_x000D_ (p=0,001) oranında azalırken, PT-yanıtsız grupta bu oran yalnızca % 11 idi (p=0,108)._x000D_ Sonuç: SLIT, ICS dozunu azaltmada etkilidir. Uzun dönemde_x000D_ ICS dozunda anlamlı azalma SLIT alanlarda mevcuttur._x000D_ Tedaviye yanıtsız olgularda SLIT alanlar yalnızca PT almış_x000D_ olanlara göre daha az süreyle ICS tedavisine gereksinim duymaktadırlar.
Ev Tozu Akarına Spesifik Dilaltı İmmunoterapi Astımlı Çocuklarda İnhale Kortikosteroid Tedavisini Sonlandırmada Ne Kadar Başarılı?